2016
DOI: 10.15252/embj.201694401
|View full text |Cite
|
Sign up to set email alerts
|

The C9orf72 protein interacts with Rab1a and the ULK1 complex to regulate initiation of autophagy

Abstract: A GGGGCC hexanucleotide repeat expansion in the C9orf72 gene is the most common genetic cause of amyotrophic lateral sclerosis and frontotemporal dementia (C9ALS/FTD). C9orf72 encodes two C9orf72 protein isoforms of unclear function. Reduced levels of C9orf72 expression have been reported in C9ALS/FTD patients, and although C9orf72 haploinsufficiency has been proposed to contribute to C9ALS/FTD, its significance is not yet clear. Here, we report that C9orf72 interacts with Rab1a and the Unc‐51‐like kinase 1 (U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

32
371
5
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(419 citation statements)
references
References 73 publications
(161 reference statements)
32
371
5
5
Order By: Relevance
“…There have been recent reports describing C9orf72’s functions in autophagy [39, 4143], including a decrease in autophagy initiation as a result of knockdown of C9orf72 [41, 42]. These observations are not necessarily mutually exclusive to our present study.…”
Section: Discussionsupporting
confidence: 59%
“…There have been recent reports describing C9orf72’s functions in autophagy [39, 4143], including a decrease in autophagy initiation as a result of knockdown of C9orf72 [41, 42]. These observations are not necessarily mutually exclusive to our present study.…”
Section: Discussionsupporting
confidence: 59%
“…Although studies in mice have indicated that C9orf72 activity is important for myeloid cell function 14,18 , a report in mouse neurons and zebrafish suggests that C9orf72 isoform A may modulate poly-Q Ataxin-2 toxicity 20 , and studies have implicated C9ORF72 in regulating autophagy 20,31,32,38 , our study provides the first direct evidence showing that gain- and loss-of-function C9ORF72 mechanisms cooperate to cause the degeneration of human motor neurons. Recent studies have shown that C9ORF72 isoform A, but not isoform B, can form a functional complex with SMCR8 and WDR41 20 .…”
Section: Discussionmentioning
confidence: 64%
“…Impairment of autophagy leads to accumulation of p62, a selective substrate of autophagy, which forms aggregates with ubiquitin (9). C9orf72 is a Rab1 effector that promotes initiation of autophagy, and disruption of C9orf72 function in cell lines and primary neurons inhibits autophagy and increased ER stress (10). This latter has been an expected finding since autophagy alleviates ER stress (11).…”
mentioning
confidence: 88%
“…O'Rourke et al showed that C9orf72 is required for normal function of myeloid cells and microglia, since loss of C9orf72 led to lysosomal accumulation and altered immune responses in macrophages and microglia (6). Also, C9orf72 depletion in HeLa cells and neurons caused accumulation of p62-positive inclusion, thus mimicking p62 pathology in ALS/FTD (10).…”
mentioning
confidence: 99%